2018
DOI: 10.5761/atcs.cr.17-00081
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Recurrent Pseudoaneurysms after Endovascular Repair of Abdominal Aortic Aneurysm in a Patient with Behçet’s Disease

Abstract: In Behçet's disease (BD) patients, endovascular repair is a reasonable alternative treatment for aortic aneurysms to avoid postoperative anastomotic pseudoaneurysms. However, there are some complications that may occur after endovascular repair. We herein report the case of a 40-year-old man with active BD developed recurrent aortic pseudoaneurysms at the proximal and distal margins of the stent graft and a femoral puncture site pseudoaneurysm 3 months after endovascular abdominal aortic aneurysm (AAA) repair.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The stent should be long enough to cover the lesion in order to seal in a healthy part of the vessel 33 . However, arterial puncture is a risk factor for pseudoaneurysm formation 23,34,35 (3 cases in our study). Moreover, data on the long-term results are limited in the literature 36 .…”
Section: Devicementioning
confidence: 58%
See 1 more Smart Citation
“…The stent should be long enough to cover the lesion in order to seal in a healthy part of the vessel 33 . However, arterial puncture is a risk factor for pseudoaneurysm formation 23,34,35 (3 cases in our study). Moreover, data on the long-term results are limited in the literature 36 .…”
Section: Devicementioning
confidence: 58%
“…Except for Balcioglu et al 37 who have not observed any aneurysm formation nor thrombosis after aortic stent graft placement after a median follow-up of 40 months, all other series have reported a recurrence rate ranging between 8.3 and 75% after endovascular procedures 18-21, 29, 34, 38-40 . Many cases of pseudoaneurysms at the proximal or distal margin of the stent graft have been described 21,35,40,41 and resulted in patient death in three cases due to rupture 19,29,40 . Despite the less invasive nature of endovascular treatment, interactions between the stentgraft and the vascular wall led to the formation of pseudoaneurysms at both ends.…”
Section: Devicementioning
confidence: 99%
“…Some experience on TEVAR for systemic vasculitis has been reported, which is proved superior to open surgery on preventing immediate complications and aortic anatomical pseudoaneurysm. However, recurrent TAP remains to be a continuing problem because of aortic wall injury or mechanical force at the edge of the stent triggering vascular inflammation [ 33 ]. It is suggested that adjunctive perioperative and postoperative immunosuppressive treatment is essential [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, endovascular treatment for aneurysms in BD is not without any risk, complications induced by chronic vascular inflammation, such as graft infection, stent occlusion and recurrent pseudoaneurysm at the margin of endograft or puncture site can be up to 40%. 2,3,5,14 This patient has been adhered to immunosuppressive therapy for many years, which is helpful to control the chronic inflammation and reduce the complications. Also, the PET/CT scan, which has emerged as a potential tool to diagnose and follow-up inflammatory AAAs, 15 demonstrated low 18 F-fluorodeoxyglucose uptake in the aorta, indicating a low activity and severity of inflammation.…”
Section: Discussionmentioning
confidence: 99%